Analysis of world experience in the use of artificial intelligence in traffic control systems at various levels - D. V. Navoi; D. V. Kapski; N. A. Filippova; I. N. Pugachev (Системный анализ и прикладная информатика, 2024)
When operating automated traffic control systems and their transformation into intelligent transport systems, modern requirements are imposed on the overall parameter safety, which characterizes the quality and efficiency of road traffic, especially when organizing high-speed loaded traffic of motor vehicles. The article discusses the use of various mathematical methods for these purposes when modeling transport processes and systems, including taking into account the development of artificial intelligence algorithms, so that when making decisions on traffic control, one can have reliable forecast indicators obtained from adequate models. A comparison of the models is made and recommendations are given on their applicability and the results obtained for traffic management purposes.